Intracycle variation in number of antral follicles stratified by size and in endocrine markers of ovarian reserve in women with normal ovulatory menstrual cycles. (31st January 2013) - Deb, S.; Campbell, B. K.; Clewes, J. S.; Pincott‐Allen, C.; Raine‐Fenning, N. J.
ABSTRACT: Objective: To quantify the intracycle variation in markers of ovarian reserve measured by antral follicle counts stratified by size using three‐dimensional (3D) ultrasound and anti‐Müllerian hormone (AMH) in women with normal menstrual cycles. Methods: Healthy volunteers with normal menstrual cycles were prospectively recruited. Three‐dimensional (3D) ultrasound examination and blood test were performed in early (F1) and mid‐follicular (F2) phases and in periovulatory (PO) and luteal (LU) phases of one menstrual cycle. Antral follicles were measured using 'sonography‐based automated volume calculation' with post processing (SonoAVC) and ovarian volume was measured using Virtual Organ Computer‐aided AnaLysis (VOCAL). Blood serum was processed for hormonal assays including AMH, follicle stimulating hormone (FSH), luteinizing hormone (LH) and estradiol. Repeated‐measures analysis was used to examine the variance in markers of ovarian reserve in different phases of one menstrual cycle. Results: A total of 36 volunteers were included in the final analysis, of whom 34 attended all four visits. Repeated‐measures analysis showed a significant variation in total antral follicle count (AFC) ( P  < 0.001). However, on stratifying the antral follicles according to size using SonoAVC, a non‐significant variation ( P  = 0.382) was seen in small AFC (≤ 6.0 mm) and a significant variation ( P  < 0.001) was seen in large AFC (> 6.0 mm). The ovarian volume showed a significant intracycle variation ( P  < 0.001). A small but significant intracycle variation was noted in AMH ( P  = 0.041) and a significant variation was seen in levels of serum FSH, LH and estradiol ( P  < 0.05). Conclusion: Small antral follicles (≤ 6.0 mm) measured using 3D ultrasound and AMH show little intracycle variation and perhaps should be evaluated when predicting ovarian reserve independent of menstrual cycle.